A 3D study of the relationship between leaf vein structure and mechanical function. (1st April 2019) - Pierantoni, Maria; Brumfeld, Vlad; Addadi, Lia; Weiner, Steve
Graphical abstract: Abstract: We investigate the structures and mechanical properties of leaf midribs of Ficus microcarpa and Prunus dulcis, which deposit calcium oxalate crystals, and of Olea europaea midribs which contain no mineral deposits, but do contain lignified fibers. The midrib mechanical performance contributes to the leaf's ability to maintain a flat conformation for light harvesting and to efficiently reconfigure to reduce wind drag. We use a novel approach involving 3D visualization of the vein structure during mechanical load. This involves the use of customized mechanical loading devices that fit inside a microCT chamber. We show that the elastic, compression and torsional moduli of the midribs of leaves from the 3 species examined vary significantly. We also observed different modes of fracture and buckling of the leaves during compression. We assess the contributions of the calcium oxalate crystals to the mechanical and fracture properties. In F. microcarpa midrib linear arrays of calcium oxalate crystals contribute to resisting the bending, in contrast to P. dulcis leaves, where the calcium oxalate crystals do not resist bending. In both F. microcarpa and P. dulcis isolated calcium oxalate crystals enable high torsional compliance. The integrated microCT – mechanical testing approach could be used to investigate the structure-mechanics relationships in other complex biological samples. Statement of significance: Leaves need to maintain a flat conformation for light harvesting, but they also need to efficiently reconfigure to reduce wind drag. The leaf central vein (midrib) is a key structural component for leaf mechanicss. 3D visualization of the vein structure under mechanical loads showed that veins can be stiffened by reinforcement units composed of calcium oxalates crystals and lignin. The stiffening units can influence the bending and fracture properties of the midribs, and can contribute to determine if buckling will occur during folding. Mineral stiffening elements could be a widespread strategy to reinforce leaf veins and other biological structures. This structural-mechanical approach could be used to study other complex biological samples.